The intricate interplay between dietary habits and cognitive function: insights from the gut-brain axis - Zhang, Ruyi; Zhang, Meiya; Wang, Pengyu (Frontiers in Nutrition, 2025)
The intricate relationship between dietary habits and cognitive function is gaining increasing attention, with a focus on the gut-brain axis as a modifiable target for intervention. This review synthesizes evidence on the impact of dietary patterns, particularly the Mediterranean diet, plant-based diets, and low-carbohydrate diets, on cognitive health. These diets, rich in antioxidants, anti-inflammatory compounds, and neuroprotective nutrients, are suggested to slow cognitive decline and reduce the risk of neurodegenerative disorders through mechanisms such as reduced inflammation and oxidative stress, and enhanced neurogenesis. The Mediterranean diet has been associated with improved cognitive performance and a delay in cognitive decline in elderly populations. However, challenges in dietary intervention implementation, including adherence and individual variability, remain. Future research must adopt a multidisciplinary approach, incorporating long-term, large-scale, multicenter randomized controlled trials to assess the enduring impacts of various dietary patterns on cognitive function, considering socioeconomic and cultural factors. This review underscores the potential of dietary interventions to prevent and mitigate cognitive impairment, ultimately aiming to improve quality of life.